Techno-Economic Modeling of Floating Wind Farms - Ariadna Montes; David Fournely; Jens N. Sørensen; Gunner C. Larsen (Energies)
A simple techno-economic model for determining wind power production and costs related to the development of floating offshore wind power is proposed. The model is a further extension of the minimalistic prediction model for fixed-bottom wind farms previously developed by two of the authors. In the extended version, costs associated with the deployment of floating structures, such as floaters, mooring lines, and anchors, including additional installation and operational expenses, are taken into account. This paper gives an overview of the costs of the various components of different types of floating wind power installations, and using actual wind climate and bathymetry data for the North Sea, the model is employed to map the annual energy production and levelized cost of energy (LCoE) for floating wind farms located in the North Sea.